Avaliação de modificações pós-traducionais de caráter redox do fungo Paracoccidioides brasiliensis após estresse nitrosativo - Navarro, Marina Valente [UNIFESP] (2017)
The fungi Paracoccidioides brasiliensis and P. lutzii are the causative agents of paracoccidioidomycosis, a systemic mycosis endemic in Latin America. This fungus is considered a facultative intracellular pathogen, able to survive and replicate inside macrophages. Its survival during infection depends on the fungus adaptability to various conditions, such as nitrosative/oxidative stress produced by the host immune cells, particularly alveolar macrophages. Currently, there is few knowledge about the P. brasiliensis signaling pathways involved in the fungus evasion mechanism of the host defense response. However, it is known that some of these pathways are triggered by reactive oxygen and nitrogen species (ROS/RNS) produced by host cells. Considering that NO (nitric oxide) effects on pathogens is concentration dependent, such effects could alter the redox state of cysteine residues by influencing (activation or inhibition) a variety of protein functions, standing out S-nitrosylation, a very important post translational modification NO dependent which regulates cellular functions and signaling pathways. It has been demonstrated by our group that P brasiliensis yeast cells proliferate when exposed to low NO concentrations. Thus, this work investigated the modulation profile of S-nitrosylated proteins of P. brasiliensis, as well as identified S-nitrosylation sites after treatment with RNS. Through mass spectrometry analysis (LC-MS/MS) and label-free quantification it was possible to identify 487 proteins on global proteome study and 474 proteins on S-nitrosylated proteome study. With this approach, we observed that proteins treated with NO low concentrations presented a proliferative response pattern, with several proteins involved with cellular cycle regulation and growth and would represent, as last analysis, molecules with an important role to fungi virulence. On the other hand, proteins stimulated with NO high concentrations exhibited a survival response pattern and may help to understand RNS antifungal properties and identify potential molecular targets to future development of new drugs.